If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 2x + 5(-1x + -4) + 3 = 8 + -3x + -2(-4x + -10) + 10 Reorder the terms: 7 + 2x + 5(-4 + -1x) + 3 = 8 + -3x + -2(-4x + -10) + 10 7 + 2x + (-4 * 5 + -1x * 5) + 3 = 8 + -3x + -2(-4x + -10) + 10 7 + 2x + (-20 + -5x) + 3 = 8 + -3x + -2(-4x + -10) + 10 Reorder the terms: 7 + -20 + 3 + 2x + -5x = 8 + -3x + -2(-4x + -10) + 10 Combine like terms: 7 + -20 = -13 -13 + 3 + 2x + -5x = 8 + -3x + -2(-4x + -10) + 10 Combine like terms: -13 + 3 = -10 -10 + 2x + -5x = 8 + -3x + -2(-4x + -10) + 10 Combine like terms: 2x + -5x = -3x -10 + -3x = 8 + -3x + -2(-4x + -10) + 10 Reorder the terms: -10 + -3x = 8 + -3x + -2(-10 + -4x) + 10 -10 + -3x = 8 + -3x + (-10 * -2 + -4x * -2) + 10 -10 + -3x = 8 + -3x + (20 + 8x) + 10 Reorder the terms: -10 + -3x = 8 + 20 + 10 + -3x + 8x Combine like terms: 8 + 20 = 28 -10 + -3x = 28 + 10 + -3x + 8x Combine like terms: 28 + 10 = 38 -10 + -3x = 38 + -3x + 8x Combine like terms: -3x + 8x = 5x -10 + -3x = 38 + 5x Solving -10 + -3x = 38 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -10 + -3x + -5x = 38 + 5x + -5x Combine like terms: -3x + -5x = -8x -10 + -8x = 38 + 5x + -5x Combine like terms: 5x + -5x = 0 -10 + -8x = 38 + 0 -10 + -8x = 38 Add '10' to each side of the equation. -10 + 10 + -8x = 38 + 10 Combine like terms: -10 + 10 = 0 0 + -8x = 38 + 10 -8x = 38 + 10 Combine like terms: 38 + 10 = 48 -8x = 48 Divide each side by '-8'. x = -6 Simplifying x = -6
| 3x+41=9x-7 | | 33x^2-22x=0 | | 2x^2-16x+3=0 | | 2x+9+7x=72 | | 17+7x=4+6x | | 3(x-5)=x+5 | | 40x=34x+2400 | | t^2+3t=54 | | y^2-19y=0 | | (z-3)(z+2)=0 | | x-43=-16 | | 3X-16=X+16 | | X+6+x=12 | | 4x-2(7-x)=-2 | | 21x^2+23x+6= | | 15-5a=5 | | 35-2/3 | | 7x-15=8-5(3x+1) | | 2((a+3b)/11) | | t-17=21 | | 40/20 | | 3x+6(8x+5)=-21 | | 5(8x+6)-2=-12 | | 5x+2=-28 | | 12(-82+26)=84(-2x+62) | | 6/17+2/8 | | n(n+7)=0 | | 5x-15=3x+24 | | 3n^2+17=0 | | 9y-10x(10y+79)=62 | | 64k^4-b^10=0 | | 9y-10x=62 |